Концептуальна модель автоматизованої інформаційної системи маркетингу на підприємстві - Райко, Діана Валеріївна; Лебедєва, Лілія Едуардівна (Сумський державний університет, 2014)
Ціллю статті є створення концептуальної моделі автоматизованої інформаційної системи маркетингу. Головна перевага цієї моделі – це забезпечення безперервного зв'язку підприємства з партнерами, споживачами та можливість оперативного реагування на ринкові зміни, а це в свою чергу сприяє підвищенню конкурентоспроможності на внутрішньому і зовнішньому ринках. Результати цієї моделі апробовані на декількох промислових підприємствах України, що підтверджує її практичну значущість.

The aim of the article. The purpose of this paper is to create a conceptual model of an automated information system of marketing that has a certain theoretical and practical value. The results of the analysis. The main advantage of this model is a comprehensive disclosure the relationship of such concepts as automated information technology, marketing information system, automated information system. They help to solve the problem of large volumes data processing in a short period of time, providing continuous communication with partners and customers and make it possible to react quickly to market changes, and this in turn contributes to the competitiveness of the domestic and foreign markets. Scientific novelty of this model is, firstly, the assertion that the information system is based on automated information technology and it presents an automated information of the system. Secondly, the marketing information system is an integral part of information system, its structural elements are responsible for the transformation of data from internal and external sources of information to information necessary for managers and specialists of marketing services. Thirdly, the most important component of ensuring the functioning of the marketing information system and information system is an automated information technology. Due to the fact that these systems consist of human resources, work within them organized with the help of workstations.
Conceptual model of an automated information system of marketing at the enterprise
Keywords: інформаційна система; автоматизована інформаційна технологія; маркетингова інформаційна система; маркетингові дослідження; information system; automated information technology; marketing information system; marketing research